Addition of Emulsifiers to Hydrogenated Soybean Oil‐Based Feeds for Yellowtail. (12th February 2018) - Bergman, Alexis M.; Trushenski, Jesse T.; Drawbridge, Mark
Abstract: Hydrogenated soybean oil can be used to spare fish oil in aquafeeds, but lipid digestibility may be a limiting factor. We evaluated the performance and tissue fatty acid composition of juvenile Yellowtail Seriola dorsalis that were fed diets containing menhaden fish oil (positive control), hydrogenated soybean oil (negative control), or hydrogenated soybean oil amended with 1% mixed bile acids, casein, whey protein, or monoglycerides as emulsifying agents. Juvenile fish ( 10 g) were stocked in a semi‐closed recirculation aquaculture system (15 fish/tank), diets were randomly assigned to tanks in triplicate ( N = 3), and fish were fed in slight excess of estimated apparent satiation amounts for 6 h/d with belt feeders. After 8 weeks, production performance was equivalent for fish fed the positive control and negative control feeds; amending the hydrogenated soybean oil‐based feeds with casein, whey protein, or monoglycerides did not affect performance, whereas adding mixed bile acids significantly impaired performance (weight gain = 655–681% versus 459%; survival = 98–100% versus 49%; feed conversion ratio = 1.19–1.22 versus 1.56). Whole‐body fatty acid composition tended to mirror dietary composition except that fish receiving the hydrogenated soybean oil‐based feeds exhibited disproportionately lower levels of saturated fatty acids and higher levels of monounsaturated fatty acids, long‐chain polyunsaturated fatty acids, and n‐3 and n‐6 fatty acids compared to dietary levels. Results suggest that casein, whey protein, and monoglycerides could be added to saturated fatty acid‐rich hydrogenated soybean oil‐based diets to reduce tissue fatty acid profile distortion, but production performance might not be enhanced. Of all the hydrogenated soybean oil‐based feeds in this study, the one supplemented with casein resulted in a whole‐body fatty acid profile closest to that of fish fed the fish oil‐based feed. Mixed bile acids should not be added due to the resulting negative impacts on survival and growth.